Whole-Genome Sequencing and Bioinformatics as Pertinent Tools to Support Helicobacteracae Taxonomy, Based on Three Strains Suspected to Belong to Novel Helicobacter Species - Berthenet, Elvire; Bénéjat, Lucie; Ménard, Armelle; Varon, Christine; Lacomme, Sabrina; Gontier, Etienne; Raymond, Josette; Boussaba, Ouahiba; Toulza, Olivier; Ducournau, Astrid; Buissonnière, Alice; Giese, Alban; et al. (Frontiers in Microbiology, 2019)
The present study describes three putative novel species received at the French National Reference Center for Campylobacters & Helicobacters (CNRCH). The CNRCH 2005/566H strain was isolated in 2005 from the feces of a patient between 55 and 60 years old with a hepatocellular carcinoma and gastroenteritis. Strain 48519 was isolated in 2017 from the blood of a male patient suffering from a bacteremia. Strain Cn23e was isolated from a gastric biopsy from a dog suffering from chronic gastritis. Biochemical and growth characteristics and electron microscopy for these three strains were studied. Their genomes were also sequenced. gyrA based phylogeny built with 72 nucleotide sequences placed CNRCH 2005/566H among the unsheathed enterohepatic helicobacters, close to Helicobacter valdiviensis; strain 48519 among the sheathed enterohepatic helicobacters, close to Helicobacter cinaedi; and strain Cn23e among gastric helicobacters, close to Helicobacter felis. 16S rRNA gene phylogeny showed similar results, but with weak discriminant strength. Average nucleotide identity and in silico DNA-DNA hybridization analyses revealed that CNRCH 2005/566H and 48519 strains belong to new putative species, but confirmed that Cn23e corresponds to H. felis. Cn23e was able to infect C57BL6 mice and to induce gastric inflammation. The genomics data, together with their different morphological and biochemical characteristics, revealed that these 2 strains represent novel Helicobacter species. We propose the following names: ‘Helicobacter burdigaliensis’, with the type strain CNRCH 2005/566H ( = CECT 8850;  =CIP 111660), and ‘Helicobacter labetoulli’, with the type strain 48519 ( = CCUG 73475;  =CIP 1111659). This study highlights that the diversity of the Helicobacteraceae family remains to be fully explored.